Village assistance towards independence in safe drinking water and healthy food - sulaiman hamzani; Syarifudin A; Niken Pratiwi (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2026)
Village in Banjar Regency faces serious challenges in providing safe drinking water to residents living along the banks of the Martapura River. Pollution from domestic and agricultural waste, coupled with limited resources, has led to limited access to safe drinking water, which increases public health risks. This community service activity aims to improve access to and quality of safe drinking water and encourage changes in community behavior regarding the provision of healthy food. The implementation method includes mapping community water sources, training in water treatment and healthy food processing, and developing a community-based drinking water supply plan involving village heads and local cadres. The results of the activity show a significant increase in access to safe drinking water from 10 families to 50 families. In addition, the "Karya Bersama" water treatment group was formed as a forum for independent drinking water management, and 10 housewives were trained in healthy food processing. Mandatory outputs include publication of an article in the Radar Banjarmasin newspaper (August 23, 2025), publication of a community service video on Duta TV (August 27, 2025), and publication of an article in the Rakat Sehat Journal. Additional outputs include copyright for the educational tool "SARI-KASI (Synthetic Fabric Filter)" with registration number EC002025119112 dated August 26, 2025. This program shows an increase in community skills in the operation and maintenance of water treatment equipment. Recommended activities are to continue technical and institutional assistance, integration into village development plans, and replication of the activity model in other areas with similar conditions.